Influence of carbon based supports on selectivity behavior of diols and propanol in Ru catalyzed glycerol hydrogenolysis - Mane, Rasika B.; Patil, S.; Shirai, Masayuki; Rayalu, Sadhana S.; Rode, Chandrashekhar V. (Applied Catalysis B: Environmental, 2017)
Activated carbon (AC) and three graphite materials were studied as supports for Ru catalyzed glycerol hydrogenolysis to propanediols and 1-propanol. Structural characteristics of AC and graphite materials were found to greatly affect the reducibility and particle size of supported Ru and hence, the activity and product distribution in glycerol hydrogenolysis. XRD of graphite materials showed distinctly (002) plane having highly organized layered structure and the peak intensity decreased in the order of Ru/KS150 > Ru/HSAG100 > Ru/KS6 due to decrease in the graphite sheet thickness. In Raman, the intense D band in HSAG100 compared to that in KS6 and KS150 samples indicated its highly amorphous nature or mixed carbon hybridization. Glycerol conversion for Ru on AC was higher than that on graphite and among different graphites, it showed a descending activity order of Ru/KS6 > Ru/HSAG100 > Ru/KS150. The product distribution for AC and HSAG100 supported Ru was similar, giving 1-propanol (45%) alongwith 1,2-propanediol (1,2-PDO) (37%) and 1,3-propanediol (1,3-PDO) (9–11%). For graphite supports, availability of Ru although bigger in size (4–5 nm), would be higher on the surface than in case of AC which formed deep hydrogenolysis products like 1-, 2- propanol, ethanol etc.
Keywords: activated carbon; Amorphous carbon; catalysis; Glycerol; Glycerol conversions; Glycerol hydrogenolysis; graphite composites; Graphite supports; Hydrogenolysis; Hydrolysis; layered structures; Particle size; Product distributions; Propanediols; Propanol; Selectivity behavior; Structural characteristics; Structural effect; Structural effects

Impairing powerhouse in colon cancer cells by hydrazide–hydrazone-based small molecule - Patil, S.; Kuman, M. M.; Palvai, S.; Sengupta, P.; Basu, S. (ACS omega, 2018)
Mitochondrion has emerged as one of the unconventional targets in next-generation cancer therapy. Hence, small molecules targeting mitochondria in cancer cells have immense potential in the next-generation anticancer therapeutics. In this report, we have synthesized a library of hydrazide–hydrazone-based small molecules and identified a novel compound that induces mitochondrial outer membrane permeabilization by inhibiting antiapoptotic B-cell CLL/lymphoma 2 (Bcl-2) family proteins followed by sequestration of proapoptotic cytochrome c. The new small molecule triggered programmed cell death (early and late apoptosis) through cell cycle arrest in the G2/M phase and caspase-9/3 cleavage in HCT-116 colon cancer cells, confirmed by an array of fluorescence confocal microscopy, cell sorting, and immunoblotting analysis. Furthermore, cell viability studies have verified that the small molecule rendered toxicity to a panel of colon cancer cells (HCT-116, DLD-1, and SW-620), keeping healthy L929 fibroblast cells unharmed. The novel small molecule has the potential to form a new understudied class of mitochondria targeting anticancer agent.